Pemanfaatan Serum Hemolisis Dengan Penambahan Reagen Anti-Rh Terhadap Kadar Enzim Serum Glutamic Pyruvic Transminase (SGPT) - Bastian Bastian; Indah Sari; Helnia Sari; Juwy Trianes (Universitas Muhammadiyah Surabaya, 2021)
Serum glutamate pyruvate transferase (SGPT) also known as alanine aminotransferase (ALT) is an enzyme found in liver cells and is effective in diagnosing hepatocellular destruction. Examination of SGPT activity using blood serum is often difficult due to insufficient blood volume or lysed serum conditions due to improper collection. This study aims to determine whether there is use of serum hemolysis using anti-rh reagents in the examination of SGPT enzyme levels. This type of research uses an experimental design - static group comparison. The sample will be taken by students of DIV Medical Laboratory Technology IKest Muhammadiyah Palembang. The research was carried out starting from patient preparation, taking examination materials, processing examination materials, analysis and examination results. The results of the ANOVA test showed that the significant value was p = 0.000. The p value obtained was p> 0.005. The results of the study found that there was a significant difference in the amount of SGPT in normal serum and serum with the addition of anti-Rh to hemolysis serum